Investigating the relationship between postoperative radiotherapy and intestinal flora in rectal cancer patients: a study on efficacy and radiation enteritis - Long, Lin; Zhang, Yexi; Zang, Jianhua; Liu, Peng; Liu, Wei; Sun, Cheng; Tian, Dan; Li, Ping; Tian, Jin; Xiao, Jun (Frontiers in Oncology, 2024)
OBJECTIVE: This study aimed to investigate the impact of radiation therapy and radiation enteritis on intestinal flora, providing insights for treatment and prevention. METHODS: Fecal samples were collected from 16 patients undergoing pelvic radiotherapy at Qingdao Hiser Hospital Affiliated of Qingdao University (Qingdao Traditional Chinese Medicine Hospital). Samples were collected before and after radiotherapy (27-30Gy), and analyzed using DNA sequencing and biostatistical methods. RESULTS: Patients with radiation enteritis showed increased α-diversity and β-diversity of intestinal flora compared to those without radiation enteritis. Differences in flora composition were observed, with higher abundance of secondary pathways such as amino acid metabolism, carbohydrate metabolism, cofactors and vitamins metabolism, and lipid metabolism. CONCLUSION: The study revealed that patients developing radiation enteritis during pelvic radiation therapy had increased diversity and abundance of intestinal flora compared to those who did not develop radiation enteritis. Additionally, patients without radiation enteritis showed significantly higher diversity and abundance of intestinal flora post-radiation compared to pre-radiation.